Investigating the impact of microservice-oriented platform configurations on application performance - Bartosz Biegajło; Dariusz Czerwiński (Journal of Computer Sciences Institute)
Effective management of containerized applications is crucial to ensuring their performance and reliability. The aim of this work was to indicate which configuration settings of the Kubernetes orchestrator have the greatest impact on microservice application performance under conditions of increased load. For each of the established configuration variants, the throughput and response time of the test application based on the microservices paradigm were measured. Research findings indicate that excessive horizontal scaling degrades application performance and that memory usage settings may play a greater role in optimizing system performance than CPU usage.